2011
DOI: 10.1242/jeb.049163
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of musculoskeletal models from in situ measurements of muscle action in the rat hindlimb

Abstract: SUMMARYMusculoskeletal models are often created by making detailed anatomical measurements of muscle properties. These measurements can then be used to determine the parameters of canonical models of muscle action. We describe here a complementary approach for developing and validating muscle models, using in situ measurements of muscle actions. We characterized the actions of two rat hindlimb muscles: the gracilis posticus (GRp) and the posterior head of biceps femoris (BFp; excluding the anterior head with v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 47 publications
(49 reference statements)
4
16
0
Order By: Relevance
“…We also considered the effects of varying attachment compliance when one endpoint dof (rotation along the mediolateral axis, (Yeo et al 2011) is released. In this situation, the dofs in the limb are matched with the dofs restrained by the transducer attachment.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We also considered the effects of varying attachment compliance when one endpoint dof (rotation along the mediolateral axis, (Yeo et al 2011) is released. In this situation, the dofs in the limb are matched with the dofs restrained by the transducer attachment.…”
Section: Resultsmentioning
confidence: 99%
“…Note that the ‘unbalanced’ stiffness considered in Figure 2F can also be achieved by scaling the force and moments differentially. For instance, for the rat hindlimb it is natural to use N/cm for the translational stiffness and N-cm/rad for the rotational stiffnesses (Yeo et al 2011). Consistent with this possibility, in our experiments we found that releasing a dof only minimally affected the measured forces and moments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations